Effectiveness and Safety of Twice Daily Versus Thrice Daily Subcutaneous Unfractionated Heparin for Venous Thromboembolism Prophylaxis at a Tertiary Medical Center. (April 2022) - Sorgi, Meghan W.; Roach, Erin; Bauer, Seth R.; Bass, Stephanie; Militello, Michael; Welch, Sarah; Lam, Simon; Reddy, Anita J.; Torbic, Heather
Background: The direct comparison of twice daily (BID) and thrice daily (TID) dosing of subcutaneous low dose unfractionated heparin (LDUH) for venous thromboembolism (VTE) prophylaxis in a mixed inpatient population is not well-studied. Objective: This study evaluated the effectiveness and safety of BID compared to TID dosing of LDUH for prevention of VTE. Methods: Retrospective, single-center analysis of patients who received LDUH for VTE prophylaxis between July and September 2015. Outcomes were identified by ICD-9 codes. A matched cohort was created using propensity scores and multivariate analysis was conducted to identify independent risk factors for VTE. The primary outcome was incidence of symptomatic VTE. Results: In the full cohort, VTE occurred in 0.71% of patients who received LDUH BID compared to 0.77% of patients who received LDUH TID ( p = 0.85). There was no difference in major ( p = 0.85) and minor ( p = 0.52) bleeding between the BID and TID groups. For the matched cohort, VTE occurred in 1.4% of BID patients and 2.1% of TID patients ( p = 0.32). Major bleed occurred in 0.36% of BID patients and 0.52% of TID patients ( p = 0.7), while a minor bleed was seen in 3.4% of BID patients and 2.1% of TID patients ( p = 0.13). Personal history of VTE ( p = 0.002) and weight ( p = 0.035) were independently associated with increased risk of VTE. Conclusion: This study did not demonstrate a difference in effectiveness or safety between BID and TID dosing of LDUH for VTE prevention.